Formation of porous Cu hydroxy double salt nanoflowers derived from metal–organic frameworks with efficient peroxidase-like activity for label-free detection of glucose. Issue 25 (14th June 2018) - Li, Ali; Mu, Xijiao; Li, Tianrong; Wen, Huang; Li, Wanchong; Li, Yuee; Wang, Baodui
Abstract : With a leaf-like MOF-5 as both a precursor and a template and copper acetate as a second precursor, CuHDS nanoflowers have been prepared for colorimetric detection of glucose. Abstract : Currently, nanomaterials with peroxidase activity have become an important colorimetric tool for biomolecular detection. However, compared with natural enzymes, the efficiency of most nanozymes is still lower. Here, with a leaf-like metal–organic-framework-5 as both a precursor and a template and copper acetate as a second precursor, hierarchical Cu hydroxy double salt (HDS) nanoflowers have been prepared and used as a label-free glucose colorimetric detection platform. We have demonstrated a scalable and facile synthesis of hierarchical Cu HDS nanoflowers, and density functional theory (DFT) calculations confirmed that there exists a hydrogen bond between the terephthalate anions and the layer OH group. The composition of Cu hydroxyl double salt is [Cu4 (OH)6 ][BDC]·2H2 O. Importantly, for the first time, the as-prepared Cu HDSs were demonstrated as peroxidase mimics to catalyze the oxidation of the enzyme substrate, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2 O2, which accompanies a color change from colorless to blue and followed classic Michaelis–Menten models. Based on these findings, a colorimetric method based on Cu HDSs that is highly sensitive and selective for the detection of glucose was developed, with a low detection limit of 0.5 μM. The clinical applicability of the sensor is also proven to be suitable for sensing glucose in blood, suggesting that Cu HDSs could be used in the construction of portable sensors for point-of-care diagnosis and on-site tests.